PENTINGNYA PARTISIPASI MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH REFLEKSI PILKADA 2024: (STUDI KASUS DI KECAMATAN MAJALENGKA KABUPATEN MAJALENGKA) - Hendri Suwarsono; Dede Riansyah; Hamzah Jamaludin (STISIP Widyapuri Mandiri, 2025)
Community participation in regional head elections is a crucial aspect of strengthening democracy and government legitimacy. This journal explores the importance of community participation in the context of the 2024 local elections, focusing on the Majalengka District Office in Majalengka Regency. Utilizing David Easton’s political system theory, this study highlights the relationship between the input of community participation and the output of public policy, as well as its impact on the quality of governance. The research employs a case study method, conducting in-depth interviews with various stakeholders, including voters, candidates for regional head, and community leaders. Through this approach, the study aims to understand the community's perceptions regarding the significance of their participation in elections and the factors influencing their level of involvement. Interview results indicate that while the community recognizes the importance of their vote, there are still obstacles that hinder broader participation. Data analysis reveals that the level of community participation is influenced by several factors, including education, political awareness, and access to information. Individuals with a better understanding of the political process tend to be more actively involved in elections. Additionally, the roles of media and community organizations in raising political awareness are identified as significant factors in encouraging participation. In the context of Easton’s theory, this research emphasizes that community participation is a vital input in the political system that affects public policy outputs. Increased participation is expected to yield policies that are more responsive and relevant to community needs, thereby enhancing government legitimacy. The study also underscores the necessity of support from various parties to create a conducive environment for community participation. In conclusion, this research indicates that achieving a better democracy requires systematic efforts to enhance community participation in the 2024 local elections. Recommendations include the implementation of political education programs and improved access to information for the community. With these measures, it is hoped that community participation will increase, ultimately strengthening the legitimacy and quality of governance in the region.